Development of a polyvinyl alcohol/sodium polyacrylate composite polymer membrane with cesium carbonate as a mobile carrier for high‐performance CO2 capture. (10th February 2022) - Ito, Fuminori; Sugimoto, Rie; Mori, Misato; Yamada, Hidetaka
Abstract: Composite polymer membranes were prepared using carbonate, polyvinyl alcohol, an acrylic acid polymer partial sodium salt cross‐linked product, and sodium polyacrylate. In this study, the factors for further improving the separation performance of these membranes for the CO2 /He mixed gas were investigated. It was confirmed that the prepared membranes did not provide stable separation under pressure unless they had a thickness of 2.0 μm. Moreover, they could not function as high‐performance separation membranes without a carbonate additive; the optimal carbonate concentration range was determined by considering the effect of the total pressure. As a result, this work produced a high‐performance, CO2 selective permeable membrane with selectivities of more than 500 and 150 at 0.1 and 0.7 MPa, respectively, for the separation of a CO2 /He (80/20) gas mixture at 85°C.